PRAANGGAPAN TINDAK TUTUR DALAM PERSIDANGAN DI KANTOR PENGADILAN NEGERI KOTA PALU - Baisu, Laode (BAHASANTODEA, 2015)
Presuppositions are studied to determine the intents of a discourse or speech. Presuppositions are assumptions or implicit interferences in certain linguistic expressions. Every conversation always uses levels of communication and implicit or explicit presuppositions or illocutionary. By making the right presuppositions, communicative values expressed in a speech can be quickly understood. The more precise the presuppositions are hypothesized, the higher the value of communication or speech. Conversely, errors in presuppositions affect the speech that may cause uncommunicative coherence. The characteristic of presupposition is something that is assumed by the speakers as the events before generating a speech. The basic characteristic of presupposition is the nature of constancy under negation. It has the intention that the presumption of a statement will remain steady (still true) although the sentence is used as a negative statement or negation. Types of presupposition are: (1) potential presuppositions, (2) factual presuppositions, (3) non-factual presuppositions, (4) lexical presuppositions, (5) structural presuppositions, (6) counterfactual presuppositions. Kata Kunci: Presuppositions, speech act, society.